2022
DOI: 10.1155/2022/3374091
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of miRNA-mRNA Pairs in Relation to TNF-α/IL-1β Induced Inflammatory Response in Intervertebral Disc Degeneration

Abstract: Objective. The determination of miRNA-mRNA pairs for intervertebral disc degeneration (IVDD) regulated by pro-inflammatory cytokines were investigated. Methods. Two dataset (accession number GSE27494 and GSE41883 from platform GPL1352) of expression profiling was downloaded from Gene Expression Omnibus (GEO). The annulus cells were isolated from annulus fibrosus in patients with degenerative disc disease. The cells were then cultured in a three-dimensional (3D) collagen containing with/without proinflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The treatments for DLBP include physiotherapy, nonsteroidal anti-inflammatory drugs, hormones and surgical interventions, all of which can only relieve LBP symptoms and cannot effectively delay the progression of IDD. [12][13][14][15] Although biological therapies, such as gene therapy, growth factor therapy, and cell therapy, have shown efficacy in the treatment of IDD, [16][17][18][19] the inflammatory and hypoxic environment within the disc results in low cell survival; 20 moreover, growth factors have a short half-life and require multiple injections, and the instability of growth factors makes injection into the disc difficult. 21 Most gene therapy requires viral vectors, which are expensive and may cause insertional mutations, produce replication-competent viruses, and induce cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The treatments for DLBP include physiotherapy, nonsteroidal anti-inflammatory drugs, hormones and surgical interventions, all of which can only relieve LBP symptoms and cannot effectively delay the progression of IDD. [12][13][14][15] Although biological therapies, such as gene therapy, growth factor therapy, and cell therapy, have shown efficacy in the treatment of IDD, [16][17][18][19] the inflammatory and hypoxic environment within the disc results in low cell survival; 20 moreover, growth factors have a short half-life and require multiple injections, and the instability of growth factors makes injection into the disc difficult. 21 Most gene therapy requires viral vectors, which are expensive and may cause insertional mutations, produce replication-competent viruses, and induce cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%